View Single Post
  #2 (permalink)  
Old June 5th, 2006, 05:12 PM
arielote arielote is offline
Authorized User
 
Join Date: Dec 2005
Location: San Nicolas, Buenos Aires, Argentina.
Posts: 14
Thanks: 0
Thanked 0 Times in 0 Posts
Send a message via AIM to arielote Send a message via MSN to arielote Send a message via Yahoo to arielote
Default

Friend:

For me the result is OK, because the expresion a^=b^=a^=b, could be analized like:

a^=b (Call it Z)

a^=b^=a^=b may be read as ((a^=b) ^= (a^=b)), equates Z ^= Z equates 0.

Regards


Ariel


---
Ariel Folonier
San Nicolas
Argentina
Reply With Quote